Taurine Memory Enhancing Activity Against Phenobarbital Induced Male White Mice by Morris Water Maze Methode - Juliani, Seri Indah; Mayefis, Delladari; Almahdy A (Nusantara Science and Technology Proceedings, 2024)
Memory decline often occurs in every individual. Data in Indonesia in 2010 there were around 7.2% of people with memory decline. Many efforts are made to improve memory. One compound that is beneficial in improving memory is taurine. This compound has several functions including as the development of the central nervous system and as a neuroprotector. Taurine is abundant in humans, mammals, and marine animals. This study aimed to determine whether taurine has memory-enhancing activity in male white mice and to determine the most effective dose (mg/kg BB) of taurine in improving memory in male white mice. The method used in this study is the Morris Water Maze method. Test animals in this study used 25 mice divided into 5 groups. Group 1 is normal, group 2 is a positive control group given encephalon tablets, and the next group is a group given taurine at doses of 10 mg/kgBB, 20 mg/kgBB, and 40 mg/kgBB. Data analysis using One Way Anova followed by Tukey Post Hoc to find out the differences from each test group. The results of this study showed that taurine at a dose of 40 mg/kgBB had a higher percentage of memory enhancers than other doses.